2010
DOI: 10.1016/j.chemosphere.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polycyclic Aromatic Hydrocarbons in kerosene and bio-kerosene soot

Abstract: Here we report a new, efficient and reliable analytical methodology for sensitive and selective quantification of Polycyclic Aromatic Hydrocarbons (PAHs) in soot samples. The methodology developed is based on ultrasonic extraction of the soot-bound PAHs into small volumes of acetonitrile, purification of the extracts through C(18) Solid Phase Extraction (SPE) cartridges and analysis by Reverse Phase Liquid Chromatography (RPLC) with UV and fluorimetric detection. For the first time, we report the convenience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…This suggests that the reduction does not apply to all the PAHs. For low biodiesel blends, Correa and Arbilla concluded that the results show great deviations (Andrade-Eiroa et al, 2000). In the Philippines, the blend consisting of 1% biodiesel and 99% petroleum diesel is currently in use in service stations.…”
Section: Comparison Of Filter Particulate Andmentioning
confidence: 99%
“…This suggests that the reduction does not apply to all the PAHs. For low biodiesel blends, Correa and Arbilla concluded that the results show great deviations (Andrade-Eiroa et al, 2000). In the Philippines, the blend consisting of 1% biodiesel and 99% petroleum diesel is currently in use in service stations.…”
Section: Comparison Of Filter Particulate Andmentioning
confidence: 99%
“…Most of the thermodynamics parameters have been obtained for gas-liquid interactions [14]. However, the magnitude of the parameters proposed cannot explain how the analytes (especially analytes with high medium polarizability) can remain inside RPLC column as long as 60 minutes (in the case of large PAHs under usual experimental conditions in RPLC) [1]. Some authors stated that RPLC is similar to classical liquid-solid chromatography for which interactions between solute and stationary phases are even weaker than in adsorption [2].…”
Section: Revision Of Traditional Approaches For Rplc Mechanismmentioning
confidence: 99%
“…Relationship found among retention time (R t ), dipole moment (μ), and Pressure (P) is given by the mathematical power function (1).…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main handicaps in this kind of research, is that although liquid chromatography (LC) and solid-phase extraction (SPE) have become the most powerful and commonly used techniques for the identification, quantification and fractioning of organic compounds in all kinds of samples, 12 the real retention mechanism of chromatographic and SPE columns is yet unknown. [13][14][15] Anyway, some helpful conclusions have been stated in literature.…”
mentioning
confidence: 99%